PENDAPATAN NON HALAL SEBAGAI SUMBER DANA KEBAJIKAN PADA BANK UMUM SYARIAH - Ernawati Ernawati (Universitas Islam Nahdlatul Ulama Jepara, 2020)
This study aims to determine the use of non-halal income in Islamic commercial banks as qardhul hasan funds. The research data are sourced from the results of the publication of Islamic banking statistics from the Financial Services Authority (OJK), and annual reports of Islamic commercial banks in 2018, with a sample of 10 banks. The data obtained are tabulated and further processed with percentages and diagrams. The research findings show that the non-halal income of Islamic commercial banks consists of interest income and penalty income. The income is not recognized as belonging to Islamic commercial banks but is treated as qardhul hasan funds and allocated for the benefit of social activities. The Contribution of non-halal income to the total qardhul hasan funds is quite high, or by 55.62 percent. Although these qardhul hasan funds are used for social purposes, they need to minimize and avoided, as BNIS's decision to eliminate the policy of payment penalties. On the other hand, needs to availability of wadiah product for depositing Islamic bank funds in conventional banks to eliminate interest revenue. This wadiah product is not based on interest rateson.